AN ANALYSIS OF SOCIAL CONFLICT BETWEEN BLACK AND WHITE SKIN IN NOVEL ‘THE HELP’ WRITTEN BY KATHRYN STOCKETT - Asrida Asrida; Waode Hanafiah; Nur Melansari (English Education Journal, 2021)
The problem statements of the research were: 1) how is the social context of author reflected in novel The Help by Kathryn Stockett; 2) how is the social life happened in the society reflected in novel The Help; 3) how is the social function of novel The Help. The research used descriptive qualitative method by applying sociology of literature approach. The technique of data collecting used note and read techniques. The results showed that there are some conflicts happened in novel The Help: 1) the context of author explained about how black maid was discriminated against by white people in Mississippi. Many kinds of discrimination towards black maids like quote in the novel said that white people assume that blacks were a disease. One of the losers was black and he became depressed because white behavior was very brutal; 2) the social life reflected in society explained about condition in Jackson, Mississippi when black maids felt uncomfortable and treated unfairly with their social life; 3) social function explained about the role of the government. In this case, the government has failed because indirectly they support white people. In Mississippi they did not have black government because they did not need blacks to participate in politics.